2007
DOI: 10.1258/004947507781524791
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tetanus at the close of the 20th century in Nigeria

Abstract: The year 2000 marked another failed World Health Organization deadline for neonatal tetanus (NNT) eradication. Existing preventive strategies can be enhanced by exploring factors involved in the persistence of the scourge. Thus, records of neonates admitted between 1996 and 2000 into the Wesley Guild Hospital, Ilesa, were analysed. Of 3051 total neonatal admissions,162 (5.3%) had NNT. Eighty-nine (54.9%) mothers had clinic-based antenatal care (ANC), but only 59 (36.4%) had tetanus toxoid (TT) vaccines. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 5 publications
10
22
0
Order By: Relevance
“…Tetanus is a vaccine preventable disease and a significant cause of morbidity and mortality in developing countries [1,2,3,4]. The disease is usually classified into neonatal and post-neonatal tetanus in the paediatric age group.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tetanus is a vaccine preventable disease and a significant cause of morbidity and mortality in developing countries [1,2,3,4]. The disease is usually classified into neonatal and post-neonatal tetanus in the paediatric age group.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that neonatal tetanus is a public health problem accounting for 400,000 deaths annually in the developing world [5]. Regardless of programs recommended by the World health organization for its elimination by the year 2000 [6], 124,000 cases and 98,000 deaths attributable to neonatal tetanus were reported between 1998 and 1999 in Africa [1]. Nigeria alone accounts for 40% of this figure in spite of gross under reporting [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some data on neonatal tetanus in western parts of Nigeria have been recently published by Ogunlesi et al [6] and Fatuga et al [7], only cases seen towards the end of the last millennium have been considered. Therefore, to assess the progress made so far in the elimination of neonatal tetanus in Nigeria, the incidence and the outcome of the disease in Zaria were examined.…”
Section: Introductionmentioning
confidence: 99%